Inhibition of EZH2 degradation as a novel approach to overcome drug resistance in acute myeloid leukemia - Göllner, Stefanie; Müller-Tidow, Carsten (Molecular & cellular oncology, 2017)
Acute myeloid leukemia (AML); EZH2; drug resistance; epigenetic; proteasome